Numerical Study of the Accumulation Dynamics of Oil Shale Thermal Decomposition Products in the Vicinity of a Heating Element; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Knyazeva A. G. Anna Georgievna (2015, 2015)
Title screen